Library Workers Experiencing or Observing Sexual Harassment in University of California Libraries is Commonplace and Commonly Unreported - Kaplan, Samantha J. (Evidence Based Library and Information Practice, 2021)
A Review of: Barr-Walker, J., Hoffner, C., McMunn-Tetangco, E., & Mody, N. (2021). Sexual harassment at University of California Libraries: Understanding the experiences of library staff members. College & Research Libraries, 82(2), 237. https://doi.org/10.5860/crl.82.2.237 Abstract Objective – To identify whether academic library workers at the University of California Libraries (UCL) system experienced or observed sexual harassment and to measure their reporting and disclosure behavior. Design – Anonymous online survey with open and closed-end questions. Setting – All UCL system campuses (Berkeley, Davis, Irvine, Los Angeles, Merced, Riverside, Santa Barbara, Santa Cruz, San Diego, and San Francisco). Subjects – All 1610 non-student employees working in UCL system were invited to participate, 579 (36%) responded. Methods – The authors engaged multiple stakeholder groups to refine and promote this census of UCL non-student workers. The survey was distributed via REDCap and remained open for six weeks of November to December 2018. All questions were optional. Certain demographic information was not collected because respondents might have been identified via deductive disclosure. The first author conducted descriptive statistical analysis and pairs of authors conducted thematic analysis. Main Results – More than half of respondents experienced or observed sexual harassment in the workplace; women were more likely to experience than observe and vice versa for men. Harassment was most likely to be exhibited by a coworker. Less than half of respondents felt that the UCL system administration considered the issue important. Nearly three out of every four respondents who had experienced harassment at work chose not to report or disclose; this did not vary significantly between women and men. Conclusion – Sexual harassment of library workers, often by other library workers, is widespread. Staff training and policies should incorporate the reality of gender harassment and commenting on a person's appearance—the two most common forms of harassment exhibited and observed.